2016
DOI: 10.1039/c6ra18601g
|View full text |Cite
|
Sign up to set email alerts
|

Selective electrochemical detection of hydroquinone and catechol at a one-step synthesised pine needle-like nano-CePO4 modified carbon paste electrode

Abstract: A pine needle-like nano-CePO4 modified carbon paste electrode was successfully constructed for simultaneous detection of hydroquinone and catechol sensitively and selectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Due to the occupation of 4 f shells in their ions, rare earth compounds exhibit unique chemical, optical and electrical properties. Dang et al [113] . used the precipitation method to synthesize pine‐needle‐like CePO 4 nanomaterials.…”
Section: Simultaneous Detection Of Hq and Ctmentioning
confidence: 99%
“…Due to the occupation of 4 f shells in their ions, rare earth compounds exhibit unique chemical, optical and electrical properties. Dang et al [113] . used the precipitation method to synthesize pine‐needle‐like CePO 4 nanomaterials.…”
Section: Simultaneous Detection Of Hq and Ctmentioning
confidence: 99%
“…17 Zhou et al reported a pine needle-like CePO 4 nanomaterial for the determination of catechol and hydroquinone. 18 Electrochemical responses were significantly improved over a CePO 4 modified electrode because of the largely improved specific surface area. Feng et al reported a CePO 4 nanotube modified electrode for hydroquinone sensing.…”
Section: Introductionmentioning
confidence: 99%
“…5 Even trace amounts of HQ may also cause hypoesthesia, puking, debility, fatigue, kidney damage and headache. [6][7][8][9] HQ is widely used in cosmetics for bleaching purposes but long-term/ excessive use may be responsible for skin damage or severe allergy. 6 Thus, a sensitive and reliable method is required to detect trace levels of HQ.…”
Section: Introductionmentioning
confidence: 99%